THE EFFECT OF YOGA GYMNASTICS ON MENSTRUAL PAIN LEVELS ON ADOLESCENT WOMEN IN JAKARTA HIGH SCHOOL - Gulo, Kristiani; Purwarini, Justina; Yesayas, Fendy (Jurnal Ilmiah Keperawatan, 2023)
psychological, social development as well as the development of signs of wrong secondary sex changes, namely the functioning of the reproductive organs marked by menstruation. Girls will experience ovulation and menstruation. Which will be accompanied by menstrual pain. This study aims to determine the effect of yoga exercise on menstrual flow in adolescent girls at SMA  Jakarta. The design of this study was pre-experimental with a one group pretest-posttest design. The population of this study were all adolescent girls in grade X who experienced menstrual paint at SMA Jakarta the sample in this study was 105 students with total sampling technique. The research analysis used the Mann-Whitney U Test were obtained with p = 0,000 while the Wilcolxon Sign test showed p = 0,000. This research concludes that there is an effect of yoga on the menstrual flow in adolescent girls at SMA Jakarta.